Inverting palladium-phosphorus Lewis pair formation: phosphonium acting as Z-type ligand - You, Lijun; Ansmann, Nils; Greb, Lutz (Angewandte Chemie. International edition, 2025)
Phosphorus-based ligands are prototypical L-type donors. Here, we introduce a Lewis acidic phosphonium cation that engages in unprecedented Z-type coordination to palladium(0). The resulting Pd→P(V) interactions are structurally unique and stronger than conventional L-type Pd─phosphine bonds, as revealed by NMR spectroscopy, x-ray crystallography, and quantum chemical analyses (NBO, ETS-NOCV, and QTAIM). It enables the formation of rare L2Z-type Pd(0) complexes with distinctive optical and electronic properties. A notably mild P─C bond forming reaction suggests an overlooked role of Z-type interactions for facilitating reductive elimination pathways.
Zuerst veröffentlicht: 25. Oktober 2025
Gesehen am 01.12.2025